Evaluation of the National Health Care Reform Program from the Perspective of Experts - Fereydoon Khayeri; Leila Goodarzi; Ali Meshkini; Ebrahim Khaki (Iran University of Medical Sciences, 2015)
Background: Health is a national priority and it is always a duty of the government to establish a good and fair health system. The National heath care system reform program and evaluation of health system reform plan funding these programs were enforced by the Honorable Minister of Health and Medical Education on May 5th, 2014. Given the importance of this issue, the present study was conducted to evaluate the implementation of 6 programs of national health system reform plan based on the main indexes of each program. Methods: This is a cross-sectional, applied study conducted from May 8th, 2014 to September 2nd, 2014. The sample of study which were selected through random sampling method included 197 hospitals affiliated to 57 universities of Medical Sciences. A standard checklist designed by experts of Commission of Ministry of Health and Medical Education, including the main indexes which after confirmation of its validity and reliability, was reviewed and monitored by the experts at the Department of Health Monitoring and Accreditation of Ministry of Health and Medical Education through observation and interview. Results: Findings of this study showed that the indicators of current health care reform have been improved related to indexes of the cost paid by hospitalized patients, promotion of natural birth, promotion of inpatient services, residency of doctors, encouraging doctors to remain in deprived areas and improvement of the quality of hoteling. The following objectives were achieved too: 'not providing medication and medical supplies and equipment from outside the hospitals' (88.5%), 'free franchise of natural birth' (90.8%), 'active participation of resident doctors according to the program and suitability of the facilities and conditions of doctors' residence at the hospitals' (60.3%), 'timely payment of doctors' salary according to the regulations and based on monitoring their performance' (81.8%), 'employing approved specialists in accordance with the type of visits and patients' (65.2%) 'operational program, Gantt chart of the program in terms of evaluation and executive measures regarding the building and facilities' (73.3%) had the most desirable condition in comparison with other indexes. Conclusion: The findings of this study showed that health care system reform program has been successful in Iran. Among the objectives of the program, promotion of natural birth has been more successful than other indexes of health care system reform program.